Gadolinium Brain Deposition in the globus pallidus and dentate nucleus after serial administrations of a macrocyclic gadolinium-based contrast agent in oncologic pediatric patients - Jonathan Carabin; Amine Bouhamama; Ana Maria Mandache; Alexandre Basle; Edouard Marie; Cécile Faure-Conter; Pierre Leblond; Didier Frappaz; Audrey Lardy-Cleaud; Frank Pilleul (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2022)
Introduction: Gadolinium deposition in the human brain, especially in the Globus Pallidus (GP) and the Dentate Nucleus (DN) has been reported after the administration of linear Gadolinium-Based Contrast Agents (GBCAs). This study aims to determine whether repeated injections of macrocyclic GBCA are associated with an increased Signal Intensity (SI) on T1-weighted sequences in the Globus Pallidus (GP) and Dentate Nucleus (DN) in oncologic pediatric patients.  Materials and methods: This retrospective monocentric cohort study included consecutive children with at least two MRIs performed after administration of macrocyclic GBCAs. The SI measurements were determined on unenhanced T1-weighted images by drawing a circular region of interest (ROI) within GP and Thalamus (TH) and DN, Pons (P), at baseline, and at last MRI. SI ratios and the differences in ratios (GP/TH) and (DN/P) between the first and last MRI calculated.  Results: Out of 413 consecutive children attending Leon Berard cancer center, 50 patients were included, and data analysis showed significantly increased GP/TH SI ratios between the first and the last MRI (p =0.0305). The DN/P SI ratios did not significantly differ between the first and the last MRI (p=0.2668).  Conclusion: This study showed an increased SI in GP after several intravenous administrations of macrocyclic GBCAs but no increased SI was identified in the DN. Although no clinical adverse effects have been reported so far, the gadolinium deposits in the brain should be carefully monitored, especially in children who still undergo neurodevelopment.